Haughton Astrobleme: A Mid-Cenozoic Impact Crater Devon Island, Canadian Arctic Archipelago - Frisch, T.; Thorsteinsson, R. (ARCTIC, 1978)
Haughton Astrobleme is a nearly circular impact crater with a diameter of about 16 km and a central uplift in Devon Island. Bedrock exposed in the crater comprised the following mainly carbonate Lower Ordovician to Upper Silurian formations in order upward: Eleanor River, Bay Fiord, Thumb Mountain, Irene Bay and Allen Bay. The Eleanor River Formation in the centre of the crater is raised about 480 m above its normal stratigraphic position outside the crater. The much shattered and faulted lower Paleozoic rocks within the crater contrast markedly with the subhorizontal surrounding strata. The Allen Bay Formation constitutes surface exposure around all but the easternmost part of the crater's border where the Thumb Mountain and Irene Bay Formations are exposed. Also exposed in the crater are two newly recognized, and as yet unnamed, formations: a polymict impact breccia that overlies the lower Paleozoic rocks, with marked angular unconformity and crops out over about a quarter of the area of the crater; and a unit of lake sediments near the western border of the crater that lies disconformably on the impact breccia and with angular unconformity on the lower Paleozoic rocks. The impact breccia is composed chiefly of carbonate rocks, but locally contains clasts of Precambrian crystalline basement from a depth estimated to be at least 1700 m. The basement clasts show varying degrees of shock metamorphism, the highest being that displayed by rocks with vesicular, flow-banded feldspar or quartz glass. Coesite has been identified in a sample of gneiss. The lake sediments are interpreted as an infilling of the crater that occurred shortly after impact. On the basis of fossils these sediments are dated as Miocene or, possibly, Pliocene. From this and other evidence, it is concluded that the impact took place in the Miocene or Pliocene.